Analisa Rasio Laporan Keuangan Untuk Menilai Kinerja Perusahaan PT. Trimuda Nuansa Citra Tbk - Budi Dharma; Raudah Azzahra Manurung; Vina Rahmanda (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to identify and explain the analysis of the financial statements of PT. Trimuda Nuansa Citra described the emergence of the Covid-19 pandemic in its early days, so that the problems faced and how to overcome them were known. As a collection in this study are the financial reports for 2019 to 2021 with samples in the form of financial reports for the period 31 December 2019 to 31 March 2020 and 31 December 2020 to 31 March 2021. The financial reports were obtained from the web idx.com. The object under study is PT Trimuda Nuansa Citra Tbk. To measure TNCT, namely the ratio of liquidity, solvency and profitability.